Phosphorus(III)-assisted regioselective C–H silylation of heteroarenes - Dingyi Wang (Nature Portfolio, 2021)
Indole C-H silylation preferentially occurs at the C3 and C2 positions, while functionalization of the benzene core (C4-C7 sites) remains challenging. Here, the authors report a regioselective C7-H silylation of indole derivatives assisted by strong coordination of the palladium catalyst with a phosphorus directing group.